Association of Glycosylated Haemoglobin Level with the Severity of Coronary Artery Disease in NSTEMI Diabetic Patients - Salim, Mahmod Mohammad; Nesa, Malik Fazila Tun; Arif, Rahman Mohammad; Delwar, Hossain Mohammad; Masum, Mandal Md Raihan (Cardiovascular Journal, 2015)
Background: Relation between diabetes mellitus and ischemic heart disease is well established. But the effect of HbA1C on severity of coronary artery disease remains uncertain in non-ST elevation myocardial infarction and diabetic patient. Objective of our study was to know the relationship of HbA1C with the severity of coronary artery disease. Methods: In this cross sectional analytical study a total of 104 NSTEMI diabetic patients were enrolled by purposive sampling. They were divided into two groups according to the level of HbA1C, Group-I patients having HbA1C<7% and Group-II patients having HbA1C >7%. Vessel score and Gensini score was calculated from coronary angiogram and compared between groups. Results: Single vessel disease were significantly higher in group-I compared to Group-II( 38.5% vs 7.7% in Group-I vs Group-II,p<0.05). Double vessel disease were higher in group-II compared to Group-I but the difference was statistically not significant (42.3% vs 48.1% in Group-I vs Group-II respectively (p>0.05). Triple vessel disease were significantly higher in group-II compared to Group- I (19.2% vs 44.4% in Group-I vs Group-II,p<0.05). Mean Vessel score was higher in Group-II compared to Group-I(1.73 ± 0.86 vs 2.50 ±0.70 in Group-I vs Group-II, p<0.05). Mean Gensini score was higher in Group-II compared to Group-I (44.6 ± 38.4 vs 76.9 ± 44.6 in Group-I vs Group-II, p<0.05). There were significant positive linear correlation between HbA1C and Vessels score and Gensini score (p<0.05). Conclusion: This study may be concluded that the presence of HbA1C >7% are associated with of severe coronary artery disease in NSTEMI with diabetes mellitus. Cardiovasc. j. 2015; 8(1): 43-48